A novel translaminar crossover approach for pathologies in the lumbar hidden zone. Issue 6 (June 2015) - Reinshagen, Clemens; Ruess, Daniel; Molcanyi, Marek; Redjal, Navid; Walcott, Brian Patrick; Goldbrunner, Roland; Rieger, Bernhard
Abstract We report eight patients with disc herniations who underwent sequestrectomy via a crossover translaminar technique. The lateral lumbar spinal canal can be divided into several regions: the subarticular, foraminal and extraforaminal zone. Due to its difficult surgical exposure, some authors refer to part of the subarticular and foraminal region as the hidden zone. Conventional approaches involve partial or total facet joint resection, introducing risk of postoperative instability. Under fluoroscopic guidance, a high speed drill was used to create a small, angled fenestration at the base of the spinous process aimed at the contralateral hidden zone. The nerve root was visualized and disc fragments were removed without facet joint violation. Patients were registered in the International Spine Registry, Spine Tango. Numeric rating scale (NRS), Oswestry disability index (ODI) and core outcome measures index (COMI) were used to evaluate outcome after 6 weeks and 3 months. Outcome was further statistically matched with the Spine Tango pool of patients who underwent sequestrectomy via conventional techniques. Postoperative CT scans showed the translaminar crossover approach with the preserved facet joints. There was significant postoperative improvement of NRS scores and ODI at all follow-up intervals. COMI achieved significant improvement at 3 months. Statistical comparison with Spine Tango data confirmed that the translaminar crossover approach matches the clinical results of the conventional techniques. This series is a proof of principle for a successful translaminar crossover approach to the lumbar hidden zone. The outcome is not inferior to conventional inter- and translaminar routes and the technique potentially offers risk reduction for postoperative instability by preserving facet joint function, especially in the case of recurrent disease.